A sea change for semiconductors. - Geppert, L. (IEEE spectrum)
Skies were blue and trade winds were steady as the SS Semiconductor set sail in early 2001. The previous year's haul had set records, and forecasters were heralding yet another banner year. But powerful forces were to shake even this vessel's sturdy timbers. A low-pressure center caused by the bursting dot-com bubble and warm moist Y2K air from around the globe stirred up a storm so violent that it shredded the mainsail. Gales of corporate malfeasance from the southwest and typhoons of terrorism from the east swept wave after wave of stock-market volatility over the decks. While many of the crew were tossed overboard, cargo destined for distant ports sat idle in the holds. It was a long time before the winds grew calm enough for the crew to repair the battered boat and limp to port. But customers there, who had also been buffeted by the foul weather, were scarce. And the ship's officers were forced to sell their cargo at a fraction of its original value. Now, almost two years after the near-fatal voyage, forecasters are again predicting blue skies, and officers and crew are guardedly optimistic that good fortune awaits in the year ahead.